NK cell activation and CD4+ T cell α4β7 expression are associated with susceptibility to HIV-1 - Machmach, Kawthar; N’guessan, Kombo F.; Farmer, Rohit; Godbole, Sucheta; Kim, Dohoon; McCormick, Lauren; Lima, Noemia S.; Henry, Amy R.; Laboune, Farida; Swafford, Isabella; Mika, Sydney K.; Slike, Bonnie M.; et al. (The Journal of clinical investigation, 2025)
We leveraged specimens from the RV217 prospective study that enrolled participants at high risk of HIV-1 acquisition to investigate how NK cells, conventional T cells, and unconventional T cells influence HIV-1 acquisition. We observed low levels of α4β7 expression on memory CD4+ T cells and invariant NK T (iNKT) cells, 2 cell types highly susceptible to HIV-1 infection, in highly exposed seronegative (HESN) compared with highly exposed seroconverter (HESC) participants. NK cells from HESN individuals had higher levels of α4β7 than did those from HESC individuals, presented a quiescent phenotype, and had a higher capacity to respond to opsonized target cells. We also measured translocated microbial products in plasma and found differences in phylum distribution between HESN and HESC participants that were associated with the immune phenotypes affecting the risk of HIV-1 acquisition. Finally, a logistic regression model combining features of NK cell activation, α4β7 expression on memory CD4+ T cells, and T-box expressed in T cells (Tbet) expression by iNKT cells achieved the highest accuracy in identifying HESN and HESC participants. This immune signature, consisting of increased α4β7 on cells susceptible to HIV infection combined with higher NK cell activation and lower gut-homing potential, could affect the efficacy of HIV-1 prevention strategies such as vaccines.